Produção de linguiça a base de atum - Jácome, Andréia Amanda Bezerra (2019)
Tuna is an excellent source of protein and has high quantity of polyunsaturated fatty acids. The production of derivatives is presented as one of the forms of consumption of this protein. The objective of this work was to evaluate the physicochemical, microbiological and sensorial quality of elaborated tuna-based sausages, as well as the feasibility of using inulin in the elaboration of these sausages and to test the use of the preservatives Sodium Lactate and Lactic Acid in their shelf life. The work was divided in two parts: in the first one, 3 formulations of sausages were elaborated: control (TS), Sausage with pork lard (TSL) and Sausage with Inulin (TSI); microbiological and physicochemical analyzes were performed on days 0, 3 and 6; was also made sensorial analysis of the sausages. In the second part, 3 formulations were also elaborated: control (TS), Sausage with Sodium Lactate (SSL) and Sausage with Lactic Acid (SLA), subjected to microbiological and physicochemical analyzes on days 0, 5, 10 and 15. It was observed that the substitution of fat by inulin caused changes in the texture of the sausages and made them less susceptible to lipid oxidation, besides showing good sensorial acceptance. The sodium lactate and the lactic acid retarded the microbial growth of the sausages, with sodium lactate having a greater effect on most of the analyzed microorganisms. The addition of inulin is viable for the production of these sausages, being seen as a good substitute for pork lard, and the use of the additives was efficient in reducing the microbial load of the sausages, making the product viable for consumption up to 15 days